The impact of technology choice on rural women in Bangladesh : problems and opportunities - Scott, Gloria L.; Carr, Marilyn (Washington, D.C., U.S.A. : The World Bank, 1985)
Increasing poverty and landlessness in Bangladesh are compelling socio-economic change. Part I of this paper provides background on the social, cultural, and economic issues relevant to the concern for increasing women's opportunities for employment and income generation in rural Bangladesh. It describes the full range of women's economic contribution and importance to the rural economy and to the consumption and welfare of their families. Some of the Government and nongovernmental programs to improve the status and skill of women in Bangladesh are described, and approaches are suggested for increasing income-earning opportunities. Part II discusses the capital and labor intensiveness of various crop-processing technologies and their impact on the employment of women. After direct crop production, post-harvest activities are the most significant source of rural employment for women, especially among landless and marginal families, those most affected by the loss of opportunity due to technological changes. The paper examines the extent, causes, and effects of technological changes in food processing (especially rice, oil seeds, and sugar) and small-scale and cottage industries (jute and silk).
Includes bibliographical references: p. 105-107.
oif 21/02/2020
Loans
Keywords: Rural women-- Employment; Agricultural processing industries; Agricultural processing industry workers